INFLUENCE OF AUDIT OPINION, FIRM SIZE, COMPANY GROWTH ON AUDITOR SWITCHING - Lumbantoruan, Peronika; Deliana , Deliana; Napitupulu, Ilham H.; Syahputra, Rizki (Jurnal Riset Terapan Akuntansi, 2025)
This study examines non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024 to investigate the influence of audit opinions, firm size, and corporate growth on auditor switching. The independent variables consist of audit opinion, firm size, and company growth, while auditor switching serves as the dependent variable. The research relies on secondary data collected through purposive sampling, resulting in 80 companies with a total of 400 firm-year observations. Logistic regression analysis was performed using SPSS 25 to process the data. According to this study, that firm size has a negative effect on auditor switching, whereas audit opinion and company growth show no affect on auditor switching. Keywords: Audit Opinion, Firm Size and Company Growth